YY1 Is a Key Player in Melanoma Immunotherapy/Targeted Treatment Resistance - Kwiatkowska, Dominika; Mazur, Ewelina; Reich, Adam (Frontiers in Oncology, 2022)
Malignant melanoma, with its increasing incidence and high potential to form metastases, is one of the most aggressive types of skin malignancies responsible for a significant number of deaths worldwide. However, melanoma also demonstrates a high potential for induction of a specific adaptive anti-tumor immune response being one of the most immunogenic malignancies. Yin Yang 1 (YY1) transcription factor is essential to numerous cellular processes and the regulation of transcriptional and posttranslational modifications of various genes. It regulates programmed cell death 1 (PD1) and lymphocyte-activation gene 3 (LAG3) by binding to its promoters, as well as suppresses both Fas and TRAIL by negatively regulating DR5 transcription and expression and interaction with the silencer region of the Fas promoter, rendering cells resistant to apoptosis. Moreover, YY1 is considered a master regulator in various stages of embryogenesis, especially in neural crest stem cells (NCSCs) survival and proliferation as it acts as a transcriptional repressor on cancer stem cell-related transcription factors. In addition, YY1 increases the metastatic potential of melanoma through negative regulation of microRNA-9 (miR-9) expression, acts as a cofactor of transcription factor EB (TFEB), and contributes to autophagy regulation, mainly due to increased transcription of genes related to autophagy and lysosome biogenesis. Therefore, focusing on the detailed biology and administration of therapies that directly target YY1 or crosstalk pathways in malignant melanoma could facilitate the development of new and more effective treatment strategies and improve patients’ outcomes.